The Peusijuek as Local Religious Wisdom: Cultural Continuity, Family Values, and Child-Centered Traditions in Acehnese Society - Veryawan Veryawan (Jurnal Anifa: Studi Gender dan Anak, 2025)
This study addresses the lack of comprehensive academic analysis on peusijuek, an Acehnese traditional ritual, particularly regarding its religious-philosophical values and its role in family and child-related traditions. Although peusijuek remains widely practiced and regarded as sacred by the Acehnese community, studies that integrate cultural, religious, and familial perspectives are still limited. This research aims to analyze the meaning and religious values embedded in the peusijuek tradition and its relevance within the Acehnese family structure. The study employs a library research method, drawing on books, scholarly journals, and relevant documents. The findings indicate that peusijuek represents local wisdom that harmoniously unites cultural practices and religious teachings, reinforcing the belief that religion and culture are inseparable in Acehnese society. Furthermore, peusijuek plays a significant role in rituals related to children, who are viewed as divine gifts, the foundation of family harmony, and the future generation of the nation. The study implies that peusijuek functions as a cultural instrument for transmitting religious values, strengthening family cohesion, and supporting early moral and social development within Acehnese society.